Intramolecular N−H⋅⋅⋅F Hydrogen Bonding Interaction in a Series of 4‐Anilino‐5‐Fluoroquinazolines: Experimental and Theoretical Characterization of Electronic and Conformational Effects. Issue 2 (4th December 2021) - Urner, Lorenz M.; Young Lee, Ga; Treacy, Joseph W.; Turlik, Aneta; Khan, Saeed I.; Houk, K. N.; Jung, Michael E.
Abstract: The 4‐anilino‐6, 7‐ethylenedioxy‐5‐fluoroquinazoline scaffold is presented as a novel model system for the characterization of the weak NH⋅⋅⋅F hydrogen bonding (HB) interaction. In this scaffold, the aniline NH proton is forced into close proximity with the nearby fluorine ( d H, F ∼2.0 Å, ∠∼138°), and a through‐space interaction is observed by NMR spectroscopy with couplings ( 1h J NH, F ) of 19±1 Hz. A combination of experimental (NMR spectroscopy and X‐ray crystallography) and theoretical methods (DFT calculations) were used for the characterization of this weak interaction. In particular, the effects of conformational rigidity and steric compression on coupling were investigated. This scaffold was used for the direct comparison of fluoride with methoxy as HB acceptors, and the susceptibility of the NH⋅⋅⋅F interaction to changes in electron distribution and resonance was probed by preparing a series of molecules with different electron‐donating or ‐withdrawing groups in the positions para to the NH and F. The results support the idea that fluorine can act as a weak HB acceptor, and the HB strength can be modulated through additive and linear electronic substituent effects. Abstract : Forced into proximity : The 4‐anilino‐5‐fluoroquinazoline scaffold is introduced as a model system for the characterization of the weak NH⋅⋅⋅F hydrogen bonding interaction. A combination of experimental (NMR spectroscopy, X‐ray crystallography) and theoretical (DFT with NBO, NCI) techniques, together with systematic structural variations, provides insights into the nature of this interaction. Selective modulation of the strength of the intramolecular NH⋅⋅⋅F interaction is demonstrated through electronic substituent effects.